Hypovitaminosis D in patients with type 2 diabetes: risk factors and association with glycemic control and established microvascular complications - Ramírez Stieben, Luis Agustín (2022)
Introduction: Several studies reported than vitamin D deficiency increases the risk of macrovascular and microvascular disease in patients with type 2 diabetes (T2DM). We investigated the plasma levels of 25OHD in adult patients T2DM, risk factors for 25OHD deficiency and the relationship between 25OHD, glycemic control and chronic complications of T2DM. Methods: A cross-sectional study was carried out, in which 25OHD levels were evaluated in adult patients (over 18 years) with T2DM. Correlation analyses were performed to evaluate the interdependence of the 25OHD with other continuous variables. A receiver operating characteristic analysis was also performed to identify cutoff values for diagnosing vitamin D deficiency. Logistic regression was performed to identify the independent association between vitamin D deficiency and the variables associated with lower 25OHD. Results: 208 patients were analyzed. The mean age of the patients was 62 years. The 25OHD level was 19 ng/ml (IQR 13.28-24.43), 59.78% had vitamin D deficiency, and 10.33% had severe deficiency. Glycemia, HbA1c, and BMI were negatively correlated with 25OHD. Cutoff point for vitamin D deficiency was 33.39 kg/m2 for body mass index (BMI), 123 mg/dl for glycemia, and 6.65% for HbA1c. In multivariate logistic regression, BMI>33.39 kg/m2 , glycemia>123.5 mg/dl, and albuminuria presented higher odds of vitamin D deficiency. Major conclusion: Vitamin D deficiency was highly prevalent among patients with T2DM. Low levels were related to higher fasting plasma glucose, higher BMI, and diabetic nephropathy.